OPTIMIZING LEARNING: A META-ANALYSIS OF TIME MANAGEMENT STRATEGIES IN UNIVERSITY EDUCATION : Received: 11th April 2024 Revised: 20th May 2024, 22th May 2024, 29th May 2024 Accepted: 30th April 2024 - Da Liu; Shihui Zhou; Xin Lu; Guanhua Yang (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This meta-analysis rigorously investigates time management strategies within university education and their impact on academic performance, student satisfaction, and self-efficacy. Covering two decades (2004-2024), it synthesizes findings from both random and nonrandom controlled intervention studies, providing a comprehensive examination of pedagogical impacts. The analysis reveals nuanced but significant enhancements across academic and personal development dimensions, with varied effect sizes (average g values). Interventions were categorized based on their primary focus—either direct time management skills enhancement or integration within broader academic and personal development strategies. Directly targeting time management proficiency was pivotal in bolstering academic performance and self-efficacy, while broader interventions significantly elevated student satisfaction. This analysis highlights the critical interplay between time management strategies, self-efficacy, and satisfaction, suggesting that tailored, skill-specific interventions can yield substantial benefits in academic contexts. The findings advocate for a holistic approach in higher education pedagogy, emphasizing the necessity of embedding effective time management training within university curricula to optimize learning outcomes and student development. This study contributes to the academic discourse on educational strategies and underscores the imperative for empirical, evidence-based approaches in curriculum design and student support services, guiding future research in educational psychology.